Quadrotor Control Via Robust Generalized Dynamic Inversion and Adaptive Non‐Singular Terminal Sliding Mode. Issue 3 (30th April 2018) - Ansari, Uzair; Bajodah, Abdulrahman H.; Hamayun, Mirza Tariq
Abstract: A robust two‐loops structured control system design for quadrotor's position/attitude trajectory tracking is proposed. The aim of the outer loop is to provide the roll/pitch tilting commands to the inner loop, which in turns generates the tilting angles that control the quadrotor's center of gravity in the horizontal plane. The outer loop utilizes Robust Generalized Dynamic Inversion (RGDI) of a prescribed asymptotically stable differential equation in the deviation function of the horizontal position coordinates from their reference trajectories. The inner loop employs an Adaptive Non‐singular Terminal Sliding Mode (ANTSM) to control the tilting angles, in addition to controlling the yaw attitude angle and the vertical position coordinate. The proposed scheme solves the singularity avoidance problems of generalized inversion and terminal sliding mode control. The stability of outer and inner loop is ensured by utilizing positive definite Lyapunov energy function for stable tracking performance against parametric variations and bounded unknown external disturbances. Numerous simulations are conducted on a six Degrees of Freedom (DoF) quadrotor model in the presence of parametric variations, un modeled dynamics, and external disturbances.